Occurrence and Timing of Subsequent Severe Acute Respiratory Syndrome Coronavirus 2 Reverse-transcription Polymerase Chain Reaction Positivity Among Initially Negative Patients. (7th June 2020) - Long, Dustin R; Gombar, Saurabh; Hogan, Catherine A; Greninger, Alexander L; O'Reilly-Shah, Vikas; Bryson-Cahn, Chloe; Stevens, Bryan; Rustagi, Arjun; Jerome, Keith R; Kong, Christina S; Zehnder, James; Shah, Nigam H; et al.
Abstract: Using data for 20 912 patients from 2 large academic health systems, we analyzed the frequency of severe acute respiratory syndrome coronavirus 2 reverse-transcription polymerase chain reaction test discordance among individuals initially testing negative by nasopharyngeal swab who were retested on clinical grounds within 7 days. The frequency of subsequent positivity within this window was 3.5% and was similar across institutions.